Distúrbios neuromusculares em cão com neosporose - Relato de caso - Galvão, André Luiz Baptista [UNESP]; D'Angelo, Giuliana Tessari; De Sá Rocha, Thiago; Burger, Camila Paes [UNESP]; De Vasconcellos, Amanda Leal [UNESP]; Karcher, Débora Emy [UNESP]; Bresciani, Kátia Denise Saraiva [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2013)
Neospora caninum is a protozoan parasite that can cause inflammatory and degenerative disorders in peripheral nerves and nerve roots dorsal and ventral in dogs, as well as the muscles. Infection is with this parasite is common in puppies and in adult dogs is difficult occurrence. Thus, the aim of this paper is to describe a case report of an adult female Rottweiler with neuromuscular disorders caused by neosporosis.
Neuromuscular disorders in dog with neosporosis - Case report
Keywords: Ataxia; Paraparesis; Protozoan